Brief Reports - Frequent BRAF or EGFR Mutations in Ciliated Muconodular Papillary Tumors of the Lung. Issue 2 (February 2016) - Kamata, Tsugumasa; Sunami, Kuniko; Yoshida, Akihiko; Shiraishi, Kouya; Furuta, Koh; Shimada, Yoko; Katai, Hitoshi; Watanabe, Shun‐ichi; Asamura, Hisao; Kohno, Takashi; Tsuta, Koji
ABSTRACT: : Introduction: : Ciliated muconodular papillary tumors (CMPTs) are recently characterized, rare peripheral nodules of the lung. These small tumors are histologically comprised of a vaguely organized mixture of nonatypical ciliated columnar cells, mucous cells, and basal cells, and consistently follow a benign clinical course. However, the histogenesis of CMPTs remains uncertain. Methods: : We performed detailed genomic analyses of 10 archived CMPT cases, using next‐generation sequencing and high‐resolution melting analysis. Results: : Mutations were identified in eight of the 10 cases (80%); four cases harbored the BRAF ‐V600E mutation, one case harbored the BRAF ‐G606R mutation, and three cases harbored deletions in exon 19 of EGFR . All of the deletions in EGFR were of the E746‐T751/S752V subtype. Conclusions: : The high prevalence of driver gene mutations in CMPTs supports the notion that these lesions are neoplastic rather than reactive or metaplastic.